Do non-performing loans matter for bank lending and the business cycle in euro area countries? - Ivan Huljak; Reiner Martin; Diego Moccero; Cosimo Pancaro (European Central Bank (ECB), 2020)
We contribute to the empirical literature on the impact of non-performing loan (NPL) ratios on aggregate banking sector variables and the macroeconomy by estimating a panel Bayesian VAR model for twelve euro area countries. The model is estimated assuming a hierarchical prior that allows for country-specific coefficients. The VAR includes a large set of variables and is identified via Choleski factorisation. We estimate the impact of exogenous shocks to the change in NPL ratios across countries. The main findings of the paper are as follows: i ) An impulse response analysis shows that an exogenous increase in the change in NPL ratios tends to depress bank lending volumes, widens bank lending spreads and leads to a fall in real GDP growth and residential real estate prices; ii ) A forecast error variance decomposition shows that shocks to the change in NPL ratios explain a relatively large share of the variance of the variables in the VAR, particularly for countries that experienced a large increase in NPL ratios during the recent crises; and iii ) A three-year structural out-of-sample scenario analysis provides quantitative evidence that reducing banks' NPL ratios can produce significant benefits in euro area countries in terms of improved macroeconomic and financial conditions.
Keywords: G21; C32; C11; 330; Euro area countries; non-performing loans; panel Bayesian VAR; hierarchicalpriors